2009
DOI: 10.3181/0902-rm-62
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-Converting Enzyme Inhibition in the Rat Model of Acute Heart Failure: Heart Function and Neurohormonal Activation

Abstract: Endothelin-1 (ET-1) has been implicated in many cardiovascular diseases, including acute heart failure (AHF) due to myocardial ischemia. Previously we described the oral endothelin-converting enzyme (ECE) inhibitor, PP36, and in this study, we investigated its cardioprotective effect in more detail, and examined the role of PP36 in the neurohormonal activation in rats that had been subjected to acute myocardial ischemia due to the microsphere embolization of coronary microcirculation. PP36 treatment (3.5 x 10(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…However, previous in vivo studies of myocardial ischemia in animal models have provided clinically relevant information [2529, 53]. In accordance with ex vivo data, each of the selective ET A R antagonists [26, 28], the nonselective ET A R/ET B R antagonist [25, 27, 28] and the ECE inhibitor [29] have been reported to suppress increases in NE levels resulting from myocardial ischemia. For example, Fraccarollo et al [26] demonstrated that long-term treatment with the selective ET A R antagonist LU135252 decreased plasma NE concentrations 12 weeks after proximal left coronary artery ligation in rats.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…However, previous in vivo studies of myocardial ischemia in animal models have provided clinically relevant information [2529, 53]. In accordance with ex vivo data, each of the selective ET A R antagonists [26, 28], the nonselective ET A R/ET B R antagonist [25, 27, 28] and the ECE inhibitor [29] have been reported to suppress increases in NE levels resulting from myocardial ischemia. For example, Fraccarollo et al [26] demonstrated that long-term treatment with the selective ET A R antagonist LU135252 decreased plasma NE concentrations 12 weeks after proximal left coronary artery ligation in rats.…”
Section: Discussionmentioning
confidence: 63%
“…Likewise, Kolettis et al [27] reported that bosentan markedly decreased serum NE levels 24 h postligation of the left coronary artery as well as the total duration of ventricular tachyarrhythmias during the delayed phase (1–24 h) postligation in rats. In addition, an orally active ECE inhibitor PP36 has been indicated to suppress cardiac tissue NE release 48 h after acute myocardial ischemia due to microsphere embolization of coronary microcirculation in rats [29]. Left ventricular contractility was partially restored and distention significantly improved by PP36 treatment in this research.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation